2017
DOI: 10.1177/0020764017746198
|View full text |Cite
|
Sign up to set email alerts
|

The role of community pharmacists in the identification and ongoing management of women at risk for perinatal depression: A qualitative study

Abstract: Pharmacists could potentially reinforce their involvement in mental health promotion activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 69 publications
4
29
0
Order By: Relevance
“…40 Different studies confirmed the capability of the pharmacist to be involved in screening programs and risk assessment services for depression. 41,42 Kondova et al 43 identified that 70% of all patients screened in a community…”
Section: Education Of the Patient And His/her Relatives/ Caregivers Gmentioning
confidence: 99%
“…40 Different studies confirmed the capability of the pharmacist to be involved in screening programs and risk assessment services for depression. 41,42 Kondova et al 43 identified that 70% of all patients screened in a community…”
Section: Education Of the Patient And His/her Relatives/ Caregivers Gmentioning
confidence: 99%
“…While the role of some specific healthcare professionals, such as pharmacists, was not specifically mentioned in regard to screening, with terminology alluding to “all” and “primary” healthcare professionals within included publications, perhaps their role in screening is implied in some recommendations. However, healthcare professionals frequently report that formal perinatal mental health education is insufficient in curricula (Elkhodr et al 2018 ; Legere et al 2017 ; Sambrook Smith et al 2019 ). Hence, there is a need to develop, evaluate and integrate purpose-designed education with input from mental health professionals and consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns surrounding screening also often include debate as to whether routine screening is acceptable (AE Buist et al 2002 ); however, a systematic review exploring acceptability among key stakeholders, demonstrated that screening is generally acceptable to perinatal women and health professionals (El-Den et al 2015 ). There is a growing body of evidence relating to PND screening by a range of health care professionals, such as physicians (Ford et al 2017 ), nurses (Segre et al 2010 ), midwives (Martin et al 2020 ), paediatricians (Byatt et al 2013 ; Chambers et al 2019 ; Currie & Rademacher 2004 ) and pharmacists (El-Den et al 2019 ; Sarira El-Den et al 2018a , b , c ; Elkhodr et al 2018 ); hence, it is often unclear which provider is responsible for screening and there is growing support for integrating early detection in all “medical settings that encounter perinatal women” (Flynn et al 2006 ). If screening is to be delivered in a variety of medical settings, then in addition to ensuring healthcare professionals working in those settings are trained, there is a need to also ensure that appropriate, site-specific follow-up and referral pathways for diagnostic assessment and treatment are also established.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Furthermore, research exploring pharmacist-led screening for mental illnesses is also emerging, with exploratory research being conducted in the areas of perinatal depression screening as well as pilot studies demonstrating the feasibility of depression screening within community pharmacy. [21][22][23][24] A recent systematic review of community pharmacist-led depression screening for adults found that while pharmacists could use screening tools to identify people living with undiagnosed depression, there was a need for more robust, high-quality research in this area to demonstrate cost-effectiveness and clinical implications. 25 There has been less research comprehensively exploring pharmacists' roles in supporting people living with severe and persistent mental illness; however, evidence in this area is emerging, with a recent systematic review highlighting pharmacists' roles in monitoring metabolic health among people living with severe mental illness and the need for further research to investigate the impact of these roles on clinical outcomes.…”
Section: 18mentioning
confidence: 99%